2016
DOI: 10.2217/cer.15.52
|View full text |Cite|
|
Sign up to set email alerts
|

Engaging stakeholders to design a comparative effectiveness trial in children with uncontrolled asthma

Abstract: Aim To present the methods and outcomes of stakeholder engagement in the development of interventions for children presenting to the emergency department (ED) for uncontrolled asthma. Methods We engaged stakeholders (caregivers, physicians, nurses, administrators) from six EDs in a three-phase process to: 1) Define design requirements; 2) Prototype and Refine; and 3) Evaluate. Results Interviews among 28 stakeholders yielded themes regarding in-home asthma management practices and ED discharge experiences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…(17,18) The CAPE is intended to support guideline recommended asthma care on ED discharge (a course of systemic corticosteroids; daily inhaled corticosteroids or other controller; as needed quick-relief inhaled medication; assess and teach appropriate inhaler technique; arrange a post-discharge follow-up appointment; and avoid known asthma triggers) and to support appropriate asthma self-management in the home. The CAPE tool uses simplified language, visual learning, and options for individualization to also facilitate communication about discharge instructions between clinicians and the child and caregiver.…”
Section: Design and Methodsmentioning
confidence: 99%
“…(17,18) The CAPE is intended to support guideline recommended asthma care on ED discharge (a course of systemic corticosteroids; daily inhaled corticosteroids or other controller; as needed quick-relief inhaled medication; assess and teach appropriate inhaler technique; arrange a post-discharge follow-up appointment; and avoid known asthma triggers) and to support appropriate asthma self-management in the home. The CAPE tool uses simplified language, visual learning, and options for individualization to also facilitate communication about discharge instructions between clinicians and the child and caregiver.…”
Section: Design and Methodsmentioning
confidence: 99%
“…The CAPE was designed using a process of contextual inquiry that engaged ED providers and administrators, ambulatory care providers, caregivers of children with asthma, and CHWs. 40 This formative work also concluded that the completion of the CAPE by existing ED staff and providers would not be feasible. The CAPE is therefore generated by ED coordinators hired specifically by the trial to serve as discharge coordinators, in consultation with both the ED providers and the patients’ caregivers.…”
Section: A Patient-centered Approach To Ed Pediatric Asthma Interventmentioning
confidence: 99%
“…Other stakeholders engaged in the study include asthma advocacy groups, insurance agencies, and government officials (34). The CHICAGO trial (35), another PCORI-funded study that builds on multiple decades of collaboration among diverse stakeholders, is investigating the impact of multiple levels of provider and patient education on asthma outcomes in children of color presenting to emergency departments.…”
Section: Addressing Pulmonary Health Disparitiesmentioning
confidence: 99%